Nurses' performance in primary care for women victims of domestic violence: an integrative review (Research, Society and Development, 2022)
For the World Health Organization (WHO), violence is defined as an act of force against oneself, another person or community. Thus, domestic violence is classified in many types. However, there are a need for nursing care aimed at this victim population. The objective of this study was to identify the role of nurses in a primary health care for victims of domestic violence, adding to the understanding of the problem to the society and the importance of welcoming victims. Theoretical study, of the integrative type, with a qualitative approach, the following databases were used for its execution: Virtual Health Library (VHL), in the databases of the National Library of Medicine of the United States (PUBMED) and in Science Electronic Librery Online (SciELO), from the crossing of the descriptors “Violence against women”; “Nursing care”; “Primary Health Care”, using the Boolean operator AND. Thus, were subsequently selected 26 scientific paper for the final analysis, to verify the  difficulty in identifying, in the use of reception and also in the search and active listening as tools to better provide a link with the woman. The themes to guide the research were: difficulties in identifying and approaching victims of domestic violence; nursing care to domestic violence. It should be noted that the lack of professional nurse training, but it is believed that care must be aligned with the entire multidisciplinary team for its quality.